Effects of Water Stress on Vegetative Development of Some Pear Varieties (Pyrus comminus L.) - Cenk KÜÇÜKYUMUK; Bahar TÜRKELİ (Yüzüncü Yıl Üniversitesi Tarim Bilimleri Dergisi)
Pear production areas have been increasing in the last years and rootstocks and new varieties which have different growing characteristics are being used. Therefore, their responses to water stress must be determined. For this purpose, one-year-old Deveci, Ankara, and Margarita pear varieties grafted on OHFx333 rootstock were used in this study. This experiment was conducted at Fruit Research Institute, MAREM, Eğirdir-Isparta, Turkey. The potted mixture used in the study consisted of 1:1:0.5 ratio of soil:peat:manure. The mixture was put into pots having 18 liter volume as equal amounts and one year old pear trees was planted. There were three different water stress treatments in the study for each variety/rootstock combination. The treatments were; D0: the soil was fully irrigated to reach field capacity in each irrigation; D1: 50% of D0; D2: 25% of D0, severe stress. Plant height, plant weight, root weight, shoot length, and shoot diameter were affected negatively depending to stress level intensity. According to the results of measurement, it was determined that Margarita variety grafted onto OHFx333 rootstock was least affected by water stress.